2015
DOI: 10.2174/1874350101508010183
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Information During Motor Control and Action Perception: A Review

Abstract: There is a whole body of research that provides evidence that the motor system plays a crucial role in controlling as well as perceiving movements. So far a lot of evidence for the interaction of action and perception derives from studies in the visual domain. However, up to now not much is known about the role of acoustic information. The focus of this review is to provide an overview regarding the role of the motor system and auditory sense during action perception and motor control. Recent theories and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…In the last few years, research pursuit of the role of sounds in interpreting complex human movement has increased markedly (for a recent special issue, see Murgia and Galmonte, 2015 ), with particular emphasis on the role of ecological sounds associated with movement ( Murgia et al, 2015 ; Pizzera and Hohmann, 2015 ; Steenson and Rodger, 2015 ). Such research has demonstrated that a variety of information can be extracted from ecological sounds by experts ( Camponogara et al, 2017 ; Sors et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, research pursuit of the role of sounds in interpreting complex human movement has increased markedly (for a recent special issue, see Murgia and Galmonte, 2015 ), with particular emphasis on the role of ecological sounds associated with movement ( Murgia et al, 2015 ; Pizzera and Hohmann, 2015 ; Steenson and Rodger, 2015 ). Such research has demonstrated that a variety of information can be extracted from ecological sounds by experts ( Camponogara et al, 2017 ; Sors et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have further investigated biological movement perception, trying to better understand the peculiarities of the ecological sounds associated with complex human movements (for a review, see Pizzera and Hohmann, 2015 ). For instance, it has been demonstrated that relying on solely auditory information expert participants can detect opponents’ movement intentions in basketball ( Camponogara et al, 2017 ) and can discriminate shot power in ball sports ( Sors et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, just recently, a review by Sors, Murgia, Santoro, and Agostini (2015) provided an overview of audio-based interventions, concluding that future studies should focus on the type of intervention and the auditory stimuli used as well as the implementation of such interventions TRAINING WITH ACOUSTIC REAFFERENCES 4 into applied sporting contexts. Taking into account auditory information of complex sporting movements, Pizzera and Hohmann (2015) provide an overview of the current literature on this topic. The authors distinguish three dimensions regarding the use of auditory information.…”
Section: Training With Acoustic Reafferencesmentioning
confidence: 99%
“…In recent years, there is a growing interest toward the role of auditory information in the perception and execution of complex movements (Murgia & Galmonte, 2015;Murgia et al, 2016;Pizzera & Hohmann, 2015;Steenson Corresponding author: fabrizio.sors@libero.it & Rodger, 2015). In particular, various studies revealed a significant influence of auditory information in different domains, such as sport (Camponogara, Rodger, Craig, & Cesari, 2017;Murgia et al, 2017;Sors, Murgia, Santoro, & Agostini, 2015) and motor rehabilitation Pau et al, 2016;Young, Rodger, & Craig, 2014).…”
Section: Highlightsmentioning
confidence: 99%